(untitled) (Perspectivas de las Ciencias Económicas y Jurídicas, 2019)
With the incorporation of the Convention on the Rights of the Child into our constitutional normative plexus, a profound modification is made in our way of analyzing the application of Children’s Rights. In the province of La Pampa, the sanction of Law 2703 that adheres to the National Law 26061 of Integral Protection of the Rights of Girls, Boys and Adolescents (NNyA) was achieved. The Dr. Juan Pablo Meaca is the Defender of Children. Within the academic sphere, for its part, in 2016 the proposal for the dictation of the Diploma in Children’s Rights was approved. However, the figure of the Child’s Lawyer throughout the country is not yet in force, despite the ratification of the Convention on the Rights of the NNyA. In this regard, we defend that it is necessary to guarantee each child legal representation, the economic resources that the State must allocate, as well as the coordination with the Bar Associations of the different circumscriptions.